Downscale fermentation for xylooligosaccharides production by recombinant Bacillus subtilis 3610. (1st February 2019) - Amorim, Cláudia; Silvério, Sara C.; Gonçalves, Raquel F.S.; Pinheiro, Ana C.; Silva, Soraia; Coelho, Elisabete; Coimbra, Manuel A.; Prather, Kristala L.J.; Rodrigues, Lígia R.
Graphical abstract: Highlights: Beechwood xylan was used to produce XOS using B. subtilis 3610 wild type and clones. The clone selected contained a secretion tag coupled to T. reesei xyn 2 gene. The XOS obtained were (1→4)-Xyl with DP 4–6. One-time impulse fed-batch mode increased the XOS maximum production at 8 h. Optimal conditions: 2.5 g/L xylan increased up to 5.0 g/L at 3 h, pH 6.0 and 43 °C. Abstract: The global demand of prebiotics such as xylooligosaccharides (XOS) has been growing over the years, motivating the search for different production processes with increased efficiency. In this study, a cloned Bacillus subtilis 3610, containing the xylanase gene xyn2 of Trichoderma reesei coupled with an endogenous secretion tag, was selected for XOS production through direct fermentation of beechwood xylan. A mixture of XOS with a degree of polymerization ranging from 4 to 6 was obtained, presenting high stability after a static in vitro digestion (98.5 ± 0.2%). The maximum production yield expressed as total XOS per amount of xylan (306 ± 4 mg/g) was achieved after 8 h of fermentation operating under one-time impulse fed-batch. The optimal conditions found were pH 6.0 and 42.5 °C, using 2.5 g/L of initial concentration of xylan increased up to 5.0 g/L at 3 h. Xylopentaose was the major oligosaccharide produced, representing 47% of the total production yield.